2020
DOI: 10.1186/s13018-020-01610-z
|View full text |Cite
|
Sign up to set email alerts
|

Labral calcification plays a key role in hip pain and symptoms in femoroacetabular impingement

Abstract: Background: Hip osteoarthritis (HOA) is the most common hip disorder and a major cause of disability in the adult population, with an estimated prevalence of end-stage disease and total hip replacement. Thus, the diagnosis, prevention, and treatment of the early stages of the disease in young adults are crucial to reduce the incidence of end-stage HOA. The purpose of this study was to determine whether (1) a relationship among the inflammatory status of labrum and synovium collected from patients with femoroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…This pathological process eventually results in characteristic damage to the labrum and acetabular cartilage, and may predispose to hip osteoarthritis (OA) 7 , 8 . Growing evidence has recently mounted over the role of FAI in the development of early OA 9 , focusing on labral deterioration and labral calcification as part of this degenerative evolution 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This pathological process eventually results in characteristic damage to the labrum and acetabular cartilage, and may predispose to hip osteoarthritis (OA) 7 , 8 . Growing evidence has recently mounted over the role of FAI in the development of early OA 9 , focusing on labral deterioration and labral calcification as part of this degenerative evolution 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We are writing in reply to Dr. Zhong's comments regarding our recent publication [1]. While we appreciate the discussion and feedback, we are also concerned that some of these comments are somewhat vague and may be misleading.…”
Section: Dear Editormentioning
confidence: 94%
“…Almost all reports published on the pathology of synovial inflammation have been conducted on the knee. However, a recent study reported that labral degeneration is positively correlated with synovial inflammation in patients with FAI [ 10 ]. Therefore, synovial inflammation may explain the occurrence of hip pain and OA progression in patients with LT.…”
Section: Introductionmentioning
confidence: 99%